Tasks of the ecological and humanistic contents in a school course of chemistry. (Journal of Educational Sciences, 2016)
In modern time, much was the importance of environmental education and upbringing. The author of the article offers for the formation of аксиосферы personality schoolboy means the school chemistry course use the ecological and humanistic content. In the search for answers to the questions of tasks students directly become sensitive to the problems of humanity and nature protection, get the real possibility to use the acquired knowledge in life. Given the definition of «chemical task ecological and humanistic content», summarizes the advantages ofsuch tasks compared to the traditional chemical tasks. Are the selection criteria for ecological and humanistic concepts for the conditions of tasks, methodological requirements and principles of chemical problems ofecological-humanistic content, which will fully implement the basic functions of teaching and upbringing, as well as form the key components of ecological culture of the person? Principles of chemical problems: humanization and humanitarization and ecological chemistry course;steady development and diversification of educational material; integration of knowledge and skills, межпредметная integration; disclosure of multi-level organization of substances, the relationship of their composition,structure, properties and application. Criteria for the selection of ecological and humanistic conceptscan be: communication with the course of chemistry; the value for the formation of the responsible attitude towards the environment; the availability, comprehensive study and multiple uses of the concepts; the direct link with the social and natural phenomena.At the main method of solution of these tasks are subdivided into the settlement, the logical (theoretical, i.e. not requiring the fulfillment of calculations and experimental; the role in the formation of the concepts oftask to clarify the content and scope of concepts; to establish or clarify the connection of this notion with the other. Among the settlement the tasks of the humanistic content can be divided into three groups. Classificationrange of presented tasks is illustrated by concrete examples. The use on the lessons of chemistry objectives with ecological and humanistic content will contribute to the establishment of экоэтической culture of schoolchildren, to help build a life on the basis of personal environmental values and meanings. The structure of this article includes: introduction, «Defining the functions and tasks in chemistry ecological and humanistic content», «Principles and criteria for the selection of tasks in chemistry ecological and humanistic content», «Kinds of tasks in chemistry ecological and humanistic content» the conclusion.
Keywords: chemical task; ecological and humanistic contents; the school of chemistry